0158 Risk perception, outcome expectancy, and treatment self-efficacy among women and men with obstructive sleep apnea (OSA). (25th May 2022) - Sharma, Akanksha; Byrne, Sean; Deng, Annan; Chu, Jen-hwa; Sands, Scott; Wellman, Andrew; Redeke, Nancy; Yaggi, Henry; Zinchuk, Andrey
Abstract: Introduction: Continuous positive airway pressure (CPAP) is the first-line therapy for OSA. CPAP improves OSA severity, sleep architecture, and daytime symptoms. The effectiveness of CPAP, however, is limited to poor adherence. Individual's risk perception, outcome expectancy, and treatment self-efficacy predict CPAP adherence. CPAP adherence also differs by sex. However, it is unknown if predictors of CPAP use are different for women and men. We thus assessed sex differences in risk perception, outcome expectancy, and treatment self-efficacy among those with OSA. Methods: Individuals enrolled to date (target n=267) in the NICEPAP study (NCT05067088), a prospective, observational cohort examining predictors of CPAP adherence, were included. Adults newly diagnosed with OSA prescribed CPAP therapy were included, while those with a need for non-CPAP therapy or unstable medical conditions (e.g., cancer receiving chemotherapy, severe lung, heart, or mental health disorders) were excluded. The exposure was sex. Co-primary outcomes were sub-scale scores from the Self-Efficacy Measure for Sleep Apnea (SEMSA) tool: Perceived Risk, Outcome Expectancies, and Treatment Self-Efficacy before starting CPAP. In addition, we assessed a comprehensive set of established psycho-social and biomedical CPAP adherence predictors using validated measures. SEMSA sub-scale scores for males and females were compared using Kruskal-Wallis statistics. Results: We analyzed data for 33 females and 19 males. Females and males were 52 (41.0, 60.5) and 52 (35.0, 58) years old respectively (median [Q1, Q3]). Ten of 33 females and 4 of 19 males were Black with majority of others being White. The apnea-hypopnea index was 17.0 (9.1, 27.0) and 19.0 (13.3, 38.4), Epworth sleepiness scale and insomnia severity index scores were 9.0 (5.0, 12.0) & 15.0 (11.0, 18.0) and 6.0 (4.0, 9.0) & 17.0 (8.0, 19.5) for females and males respectively. There were no statistical differences in scores of Perceived Risk 2.4 (1.6, 2.9) vs 2.1 (1.8, 2.5) (p=0.717), Outcome Expectancies 2.8 (2.3, 3.4) vs 3.3 (2.4, 3.5) (p=0.371) or Treatment Self-Efficacy 3.1 (2.3, 3.7) vs 3.1 (2.0, 3.5) (p=0.977) for females vs. males. Conclusion: We found no statistically significant differences in determinants of self-efficacy between women and men. Our findings may reflect a small sample size recruited to date or that self-efficacy of CPAP therapy is independent of sex. Support (If Any): This work was supported by Parker B. Francis Foundation and National Heart, Lung, and Blood Institute/NIH (1K23HL159259-01).